Corporate Social Responsibility (CSR) and Employee Retention of Manufacturing Firms in Nigeria - okere, wisdom (JABE (JOURNAL OF ACCOUNTING AND BUSINESS EDUCATION), 2024)
This study conducted an empirical investigation on the impact of Corporate Social Responsibility on employee retention among manufacturing firms in Nigeria. Secondary data was engaged to analyze the impact of CSR on employee retention, which was sourced from ten listed manufacturing firms in Nigeria. The study engaged panel regression analysis and Pearson correlation analysis. Further results obtained from the panel regression analysis show that employee-training costs affect significantly positively on employee retention. These results are consistent with Galbreath, 2008; Evans & Davis, 2011; Odumeru & Ogbonna, 2013; Marika, Magutu & Munjuri, 2017, who found that CSR significantly influences employee retention. The study recommends that corporate organizations in Nigeria should be socially responsible to their environment and their employees; so as to attract more talents needed to remain competitive. From the study, the concept of CSR will be viewed as a social instrument which manufacturing firms use to retain employees in their organization.